Negotiating multiple identities : shame and pride among Japanese returnees - Sueda, Kiyoko (Springer Singapore Imprint: Springer, 2014)
This book uses a post-modern approach to explore how Japanese returnee students (kikokushijo) and former returnees who work in Japanese industry, negotiate multiple identities. Methodological triangulation is used to study inner perception of face, emotional state and the dynamics of negotiating multiple-layering of identities. The work considers the relationship between face and identities, and the function of the affective aspects of face, shame and pride in identity negotiation. Readers will discover how Japanese returnees deal with shame and pride in face-threatening or face-promoting situations that affect their identity negotiation. Many such returnees stayed abroad because of their parents' jobs, and the author explores variations among them, in terms of how they identify with their identity as a returnee. We discover how there are multiple levels of identities instead of 'identity' as a singular. Two phases of research, carried out across ten years and involving some participants in both phases, are explored in this work. Although the participants in the research are Japanese returnees, the findings drawn from the study have implications for others who spend an extensive period of time overseas, who migrate from one place to another, or who have multiple cultural backgrounds. The book incorporates ideas from Western and Eastern literature on intercultural communication, sociology and social psychology and it blends both micro and macro analysis. This book is recommended for scholars, educators, students and practitioners who seek to understand better how people negotiate their multiple identities in this globalising world.